2019
DOI: 10.1007/s12639-019-01094-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of haemoprotozoan diseases in cattle of Cauvery delta region of Tamil Nadu

Abstract: A study was carried out to determine the prevalence of haemoparasites in cattle in Cauvery delta region over a period of one year. A total of 228 giemsa stained blood smears were screened for the presence of haemoprotozoa, out of which 34 animals were found to be positive. An overall prevalence of haemoparasites in the sampled cattle were 14.9%, among this Anaplasma sp (8.3%), Babesia sp (3.95%), Theileria sp (2.19%) and Trypanosoma sp (0.44%) as single or mixed blood parasitic infections. In this study Anapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
(7 reference statements)
2
6
0
Order By: Relevance
“…The hematological changes observed in these cattle are indicative of significant RBCs destruction, anemia (reduced Hb level) and leukopenia in infected cattle compared to non-infected cattle (Table 2). These changes are associated with the capability of infecting parasites to reach the circulation and invade the RBCs and corroborates with earlier findings from mixed infected cattle of southern India (Jayalakshmi et al 2019). The severity of changes varied depending upon the type and degree of RBCs infected by these parasites.…”
Section: Resultssupporting
confidence: 90%
“…The hematological changes observed in these cattle are indicative of significant RBCs destruction, anemia (reduced Hb level) and leukopenia in infected cattle compared to non-infected cattle (Table 2). These changes are associated with the capability of infecting parasites to reach the circulation and invade the RBCs and corroborates with earlier findings from mixed infected cattle of southern India (Jayalakshmi et al 2019). The severity of changes varied depending upon the type and degree of RBCs infected by these parasites.…”
Section: Resultssupporting
confidence: 90%
“…It was observed that cattle infected with these parasites adversely affected haematological parameters. These changes are associated with capability of infecting parasite to reach the circulation and invade the RBCs and corroborates with earlier findings from mixed infected cattle of southern India (Jayalakshmi et al 2019). Severity of changes varied depending upon the type and degree of RBCs infected by these parasites.…”
Section: Discussionsupporting
confidence: 91%
“…Anaplasmosis is a rickettsial disease transmitted biologically through ticks mainly by Rhipicephalus (Boophilus) microplus [ 2 ]. It is endemic in some parts of the world [ 3 , 4 ] while in India incidence of A. marginale infection has been recorded in livestock [ 5 – 7 ]. The Theileria species that infect bovines in India are T. annulata and T. orientalis , and both species are transmitted by Hyalomma anatolicum .…”
Section: Introductionmentioning
confidence: 99%